ANALISIS PERALATAN BENGKEL KERJA KAYU SMK NEGERI 5 SUNGAI PENUH - 524-533, Perta Mulya Putra (Universitas Negeri Padang, 2014)
Abstract This research is aquantit ative study with quantitative descriptive method that aim stolook at the factsandin accordancewiththe actualreality. The populationin this study, namely: woodworkshopequipmentinvocational highschools5Sungai Penuh. Sampleswere takentotal sampling thew oodworkshop equipmentinvo cational highschools5Sungai Penuh. The data usedare primary dataandsecondary data. Primary datawas obtained directlyonthe woodworksh opandt hroughinter viewswiththe headteachera ndworkshoppr acticewo odentimber, while thesecondary dataobta inedthrough documents andinven toryexisting equipmentinthe woodworkshop. Data analysis techniquesusedare: quantitative edescri ptiveanalysis. The analysis showedthat thecondition ofthe existing equipmentin the workshop of vocational highschool5Sungai Penuhgenerallycategorized asfit for use, butthemanual equipmentsuch asplaners, saws, chisels, hammers, elbows,mete randmiserst illneededso meaddition alnumber oftools. Key word : Analysis,Tools, WoodWorkshop.